2016
DOI: 10.3390/ijms17060821
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fingerprinting to Assess the Impact of Salinity on Carotenoid Content in Developing Tomato Fruits

Abstract: As the presence of health-promoting substances has become a significant aspect of tomato fruit appreciation, this study investigated nutrient solution salinity as a tool to enhance carotenoid accumulation in cherry tomato fruit (Solanum lycopersicum L. cv. Juanita). Hereby, a key objective was to uncover the underlying mechanisms of carotenoid metabolism, moving away from typical black box research strategies. To this end, a greenhouse experiment with five salinity treatments (ranging from 2.0 to 5.0 decisieme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…These authors proposed a salinity-induced stimulation of the accumulation of starch during early fruit development, enhancing soluble solids content in ripe fruits (Yin et al, 2010). Other independent studies have shown that higher dry matter, sugar, and organic acid concentrations can be observed upon increasing salinity treatments (Wu & Kubota, 2008;Van Meulebroek et al, 2016). Also, there may be a correlation of the aforementioned effects on tomato fruits, the decreased photosynthesis capacity, and a change in biomass partitioning between different sink tissues as a result of salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors proposed a salinity-induced stimulation of the accumulation of starch during early fruit development, enhancing soluble solids content in ripe fruits (Yin et al, 2010). Other independent studies have shown that higher dry matter, sugar, and organic acid concentrations can be observed upon increasing salinity treatments (Wu & Kubota, 2008;Van Meulebroek et al, 2016). Also, there may be a correlation of the aforementioned effects on tomato fruits, the decreased photosynthesis capacity, and a change in biomass partitioning between different sink tissues as a result of salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…De Pascale et al (2001) and Wu & Kubota (2008) reported that moderate salinity (40-60 mM) had a positive effect on lycopene accumulation, while Massaretto et al (2018) found that lycopene concentration increased under high salt stress (100 mM) in both a commercial cultivar and a tomato landrace. On the contrary, a negative or marginal effect on carotenoid accumulation was reported under salt stress (Dorais et al, 2000;Krauss et al, 2006;Van Meulebroek et al, 2012;Van Meulebroek et al, 2016;Ehret et al, 2013). Even when carotenoids content variation in response to salinity seem to correspond to a cultivar-dependent characteristic, it might be related to the ability of the plant to cope with stress and oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although most research confirms the growth of Lyccontent in salinity conditions [69][70][71], there are a few studies that infirm this hypothesis [23,72]. Therefore, the genetic requirements and the specific conditions in which the genotype was cultivated are decisive factors on the capacities of biosynthesis of Lyc, alongside other evident factors such as ripening stage and cultivation technologies (e.g., field/greenhouse, organic/non-organic) [32].…”
Section: Assessment Of Tpc Lyc and Asacontentmentioning
confidence: 99%
“…For example, [ 72 ] investigated how the metabolome of tomato fruits changes with different salinity levels and observed carotenoid accumulation with higher salinity. [ 71 ] found plastic responses of leaves of different maize lines to different temperature conditions and identified metabolites associated with heat and cold stress.…”
Section: Bridging the Gap Between Biochemistry And Ecologymentioning
confidence: 99%